225k views
0 votes
Find the following products:

i. (x- 1)(x+ 1)
ii. (x- 1)(x2 + x + 1)
iii. (x- 1)(x³ + x² + x + 1)

User Tomi
by
4.6k points

1 Answer

6 votes

Answer:

i. x^2 – 1

ii. x^3 – 1

iii. x^4 - 1

Explanation:

Products are obtained by multipliyng each left term by each rigth term as follows:

i. (x- 1)(x+ 1) = (x^2 – x + x - 1) = x^2 – 1 (equal terms with opposite sign substracts and the result is 0)

ii. (x- 1)(x^2 + x + 1) = (x^3 – x^2 + x^2 – x + x – 1) = x^3 – 1

iii. (x- 1)(x³ + x² + x + 1) = (x^4 – x^3 + x^3 – x^2 + x^2 – x + x – 1) = x^4 - 1

User Blarg
by
4.8k points